Investigation of kinetics and mechanistic insights of the reaction of criegee intermediate (CH2OO) with methyl-ethyl ketone (MEK) under tropospherically relevant conditions. (January 2023) - Debnath, Amit; Rajakumar, Balla
Abstract: The temperature-dependent kinetics was investigated for the reaction of the simplest Criegee intermediate (CH2 OO) with Methyl-ethyl ketone (CH3 COC2 H5, MEK). A direct method was employed to measure the rate of change of the concentration of CH2 OO using a highly sensitive Pulsed Laser Photolysis-Cavity Ring-down Spectroscopy (PLP-CRDS) technique. The temperature dependent rate coefficient obtained for the CH2 OO + MEK reaction was k 4 (T = 258–318 K) = (1.26 ± 0.16) × 10 −14 × exp(1179.1 ± 71.8)/T cm 3 molecule −1 s −1 and the rate coefficient at room temperature was k 4 (298 K) = (6.39 ± 0.20) × 10 −13 cm 3 molecule −1 s −1 at 50 Torr/N2 . Theoretical calculations were performed to predict the reaction mechanism and probable end products. The secondary ozonide (SOZ) formation pathway was found to be the rate determining step, which gets decomposed into HCOOH and MEK as the major products. Both experimental and theoretical results show a negative T-dependency in the studied range. Graphical abstract: Image 1 Highlights: Gas-phase kinetics of criegee intermediate with MEK was investigated. Temperature dependent rate coefficients were measured using PLP-CRDS technique. Kinetics and thermochemistry were assessed using CVT/SCT/ISPE. Atmospheric implications of the studied reactions were examined based on the cumulative atmospheric lifetime of MEK. The MEK removal rate from the troposphere by CH2 OO and OH radicals was compared.